Mesenchymal stem cell‐coated sutures enhance collagen depositions in sutured tissues. Issue 2 (March 2014) - Casado, Javier G.; Blazquez, Rebeca; Jorge, Inmaculada; Alvarez, Veronica; Gomez‐Mauricio, Guadalupe; Ortega‐Muñoz, Mariano; Vazquez, Jesus; Sanchez‐Margallo, Francisco M.
Abstract Sutures are commonly used for surgical procedures and new sutures are being developed to improve wound healing. In the past decade, it has been extensively shown that mesenchymal stem cells (MSCs) have a wound healing potential. To benefit the overall wound healing process, we aimed to analyze the usage of pretreated sutures for improving the implantation of MSCs in the tissues. Our results firstly showed that suture pretreatments with gelatin, poly‐L‐lysine, and NaOH improved the adhesive strength of MSCs to sutures. These cells remained surrounding the sutured tissue and no significant phenotypic changes were found in those cells cultured onto pretreated sutures. In vivo experiments showed that the implantation of MSCs by suturing increases the collagen content in the sutured tissue. Moreover, proteomics analysis of secreted proteins showed that collagen alpha‐1(I) chain was the most abundant collagen found. To our knowledge, this is the first report that aimed to improve the implantation of MSCs in tissue by suture pretreatments. Moreover, in vivo experiments suggest that MSC‐coated sutures may enhance wound healing and tissue remodeling through the release of different collagen types being applicable for those patients that tend to have difficulty healing.